Vodnik po ekskurziji Ob 50. obletnici ustanovitve Paleontološkega inštituta Ivana Rakovca ZRC SAZU - Debeljak, Irena (ZRC SAZU, Založba ZRC, 1999)
This brochure was published for the 50th anniversary of the Institute of Paleontology and contains three contributions. The first and the second contribution describe two paleontological sites (of Upper Cretaceous dinosaurs and Upper Jurassic corals, respectively), that were visited during a field-trip organized on this occasion. The third contribution is a brief history of the institute.